Frontiers and hotspots in comorbid epilepsy and depression: a bibliometric analysis from 2003 to 2023 - Liu, Gui-Yu; Fu, Fan-Jia; Chou, Ying-Xin; Ye, Ming-Sha; Ouyang, Yi-Lin; Yan, Ming-De; Pan, Lei; Li, Wei-Peng; Xie, Wei (Frontiers in Neurology, 2024)
Background: Epilepsy ranks among the most common neurological disorders worldwide, frequently accompanied by depression as a prominent comorbidity.This study employs bibliometric analysis to reveal the research of comorbid epilepsy and depression over the past two decades, aiming to explore trends and contribute insights to ongoing investigations.: We conducted a comprehensive search on the Web of Science Core Collection database and downloaded relevant publications on comorbid epilepsy and depression published from 2003 to 2023. VOSviewer and CiteSpace were mainly used to analyze the authors, institutions, countries, publishing journals, reference co-citation patterns, keyword co-occurrence, keyword clustering, and other aspects to construct a knowledge atlas. Results: A total of 5586 publications related to comorbid epilepsy and depression were retrieved, with a general upward trend despite slight fluctuations in annual publications. Publications originated from 121 countries and 636 institutions, with a predominant focus on clinical research. The United States led in productivity (1529 articles), while Melbourne University emerged as the most productive institution (135 articles). EPILEPSY & BEHAVIOR was the journal with the highest publication output (1189 articles) and citation count. Keyword analysis highlighted emerging trends, including "recognitive impairment" and "mental health", indicating potential future research hotspots and trends.This study is one of the first to perform a bibliometric analysis of the 20-year scientific output of comorbid epilepsy and depression. While research has trended upwards, ambiguity in pathogenesis and the absence of standardized diagnostic guidelines remain concerning. Our analysis offers valuable guidance for researchers, informing that this might be a strong area for future collaborations.